Resectable invasive IPMN versus sporadic pancreatic adenocarcinoma of the head of the pancreas: Should these two different diseases receive the same treatment? A matched comparison study of the French Surgical Association (AFC). Issue 9 (September 2017) - Duconseil, P.; Périnel, J.; Autret, A.; Adham, M.; Sauvanet, A.; Chiche, L.; Mabrut, J.-Y.; Tuech, J.-J.; Mariette, C.; Régenet, N.; Fabre, J.-M.; Bachellier, P.; et al.
Abstract: Purpose: To compare survival and impact of adjuvant chemotherapy in patients who underwent pancreaticoduodenectomy (PD) for invasive intraductal papillary mucinous neoplasm (IIPMN) and sporadic pancreatic ductal adenocarcinoma (PDAC). Methods: From 2005 to 2012, 240 patients underwent pancreatectomy for IIPMN and 1327 for PDAC. Exclusion criteria included neoadjuvant treatment, pancreatic resection other than PD, vascular resection, carcinoma in situ, or <11 examined lymph nodes. Thus, 82 IIPMN and 506 PDAC were eligible for the present study. Finally, The IIPMN group was matched 1:2 to compose the PDAC group according to TNM disease stage, perineural invasion, lymph node ratio, and margin status. Results: There was no difference in patient's characteristics, intraoperative parameters, postoperative outcomes, and histologic parameters. Overall survival and disease-free survival times were comparable between the 2 groups. In each group, overall survival time was significantly poorer in patients who did not achieve adjuvant chemotherapy ( p  = 0.03 for the IIPMN group; p  = 0.03 for the PDAC group). In lymph-node negative patients of the IIPMN group, adjuvant chemotherapy did not have any significant impact on overall survival time (OR = 0.57; 95% CI [0.24–1.33]). Considering the whole population (i.e. patients with IIPMN and PDAC; n = 246), patients who did not achieve adjuvant chemotherapy had poorer survival ( p  < 0.01). Conclusions: The courses of IIPMN and PDAC were similar after an optimized stage-to-stage comparison. Adjuvant chemotherapy was efficient in both groups. However, in lymph node negative patients, adjuvant chemotherapy seemed not to have a significant impact.